فجوات الهوية الشخصية لدى طلبة المرحلة الاعدادية - منشد, حسام محمد; محمد, اسراء كاظم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The current research aims to identify personal identity gaps among middle school students. The research sample consisted of (500) male and female students, who were randomly selected using proportional distribution. To achieve this goal, a personal identity gap scale was constructed based on Hecht's (2005) theory. The final version consisted of (23) items. The psychometric properties of the scale were extracted, including validity and reliability, and appropriate statistical methods were used to extract the results of the current research. The results of the current research indicated that middle school students are not characterized by personal identity gaps. There is no difference in personal identity gaps according to the variables of gender (male-female) and specialization (scientific or literary) . The research resulted in a set of recommendations and suggestions for future studies.